Resin coating, an alternative in dentinal sealing techniques: A literature review (Research, Society and Development, 2024)
Resin coating is a dentin sealing technique, used in a wide branch of dentistry. This technique was invented in Japan in the early 1990s by doctors who were experts in adhesive systems, which have had great evolution over the years. However, having a wide spectrum of adhesive systems, in the resin coating technique the self-etch adhesive is recommended. After countless investigations, it was possible to discover the existence of a new zone that improves adhesion, called the acid-base resistant zone (ABR), which is created by the penetration of the monomer into the dentin and thanks to the chemical bond with the smear particles. dentin, it must be considered that this is only produced thanks to self-etching adhesive systems. This technique has also helped in different areas of dentistry and not only in dental surgery, such as endodontics, prosthodontics, and even a new thin film system has been developed, to be able to have a better result in indirect restorations and so that they do not interfere. because of its thickness.